Modelling of sediment transport pattern in the mouth of the Rhone delta: Role of storm and flood events. (5th November 2017) - Boudet, L.; Sabatier, F.; Radakovitch, O.
Abstract: The delta of the Rhone River is one of the most important in the Mediterranean Sea. Beach erosion problems along its coasts have developed in recent decades, raising the need for a better understanding of the sediment transport processes at the Rhone mouth and the adjacent beaches. Because field data are very difficult to obtain in such an energetic environment, a high-resolution numerical model (Delft3D) is applied to this area. This model is calibrated by taking into account hydrodynamical and morphological observations. Special attention is given to storm and flood events, which are the major morphological drivers. Therefore, scenarios with different wave and flow conditions are run to estimate the influence of these events on the sediment transport. The analysis of historical hydrological data shows that storms from the southeast represent 70% of the events between 1979 to 2010 and that 20% of them were followed by a flood within a few days. Consequently, specific simulations for such conditions are performed using Delft3D. The model simulates trends in the bedload sediment transport that are consistent with the bedforms observed in the bathymetry data. The total sediment transport at the outlet is only influenced by the river flow, but sediment transport at the mouth-bar depends on an equilibrium between the influence of floods and storms and the succession of these events. A period of 2 or 3 days separating the storm and flood peaks is sufficient to differentiate wave and river flow-induced sediment transport. The waves constrain the total transport on the mouth-bar and shallow mouth-lobe and induce a longshore transfer towards the adjacent beaches. The riverine sediments can be exported seaward only if a flood is energetic enough compared to the storm intensity. Regardless, when a flood is greater than the decadal return period (7800 m 3  s −1 ), the sediment is transported from the outlet across the mouth-bar and is directed offshore. Graphical abstract: Highlights: Waves constrain the transport on the mouth-bar and induce a longshore transfer. The succession on storm and flood controls the sediment transport pattern. A delay between storm and flood peak does not favour the feeding of adjacent beaches. Riverine sediments can be exported seaward only if a flood is energetic enough.